Studies on Lanthanide Mixed Complexes - Meshram , U.M.; Ramchandra Rao, V. (Asian Journal of Chemistry, 2010)
A few heptacoordinated mixed ligand complexes of the type [Ln(L) (L´)3Cl2]Cl·nH2O where Ln= Y(III), La(III), Pr(III), Nd(III), Sm(III), Gd(III) and Dy(III), L=diacetylmonoxime, L´ ═ thiourea, N-phenylthiourea and N,N´-diphenylthiourea and n ═ 3 or 4 have been prepared and characterised by elemental analysis, electronic spectra, IR, thermoanalytical and conductivity measurements.